Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Find the sum of 1/((n)(n-1)) from n = 1 to 100

  1. Jan 27, 2004 #1
    Find the sum of 1/((n)(n-1)) from n = 1 to 100.

    Any idea?
  2. jcsd
  3. Jan 27, 2004 #2


    User Avatar
    Staff Emeritus
    Science Advisor
    Gold Member

    Partial fractions!
  4. Jan 28, 2004 #3
    write 1= n-(n-1)
  5. Jan 28, 2004 #4


    User Avatar
    Science Advisor

    One "idea" I have is that the sum does not exist. The fraction is undefined when n= 1. Did you mean to start at n= 2 or would you prefer to use 1/n(n+1)? (which would be the same thing)
  6. Jan 29, 2004 #5
    Let SUM=∑k=2 to n [1/(k(k-1)] (1)

    Apart from the straightforward method using partial fractions the seeked sum can be found from a more general approach (as a particular solution).




    S=∑k=2 to n [ln(x+k)-ln(x+k+1)]=ln(x+2)-ln(x+n+1)

    By deriving both members --->

    S'=∑k=2 to n [1/(x+k)(x+k+1)]=[(n-1)/(x+2)(x+n+1)]

    If we put now x=-1 results:

    SUM=∑ k=2 to n [1/(k(k-1)]=(n-1)/n=1-(1/n) (2)

    The adavantage of this method is clear,the general formula depending on x can be particularized to find other sums,∑ k=1 to n [1/(k(k+1)] for example,and so on.
    Last edited: Jan 29, 2004
  7. Jan 29, 2004 #6
    There is another solution based on the theory of inhomogeneous sequences.The sum (depending only by 'n') must be seeked in the form:

    SUM=(A/n2)+(B/n)+C (1)


    We know that:

    S[n=2]=1/2 (2)

    S[n=3]=2/3 (3)

    S[n=4]=3/4 (4)

    s[n=5]=4/5 (5)

    S[n=6]=5/6 (6)

    Introducing (1) in (2) (3) & (4) and solving the system --->


    Therefore SUM=(-1/n)+1=1-(1/n) (7)

    Introducing now in (7) n=5 ---> S[n=5]=4/5 that is exactly (5) (for n=6 we obtain again an equality).The solution obtained is exact and holds for all values of 'n' (actually the inhomogeneous theory requires to prove that the sequence made with the free terms-here the general terms in 'n'=[1/(n(n-1))]-constitute a linear sequence but in practice it is enough to show that the obtained equation S=f(n) holds exactly for n greater than the values used to calculate the constants).
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook